Common ion effect enhanced Prussian blue analogues for aqueous ammonium ion storage. Issue 19 (28th April 2021) - Li, Siyun; Xia, Maoting; Xiao, Chengxiang; Zhang, Xikun; Yu, Haoxiang; Zhang, Liyuan; Shu, Jie
Abstract : On the basis of the common ion effect, Fe2 (SO4 )3 is utilized as a functional additive in an electrolyte to enhance the electrochemical performance of FeFe(CN)6 in aqueous NH4 + batteries. Abstract : In order to meet the growing demand of energy storage for the power grid, aqueous NH4 + batteries are attracting increasing attention as a promising alternative due to their environmental significance, abundant resources, and fast diffusion ability. In this work, FeFe(CN)6 (FeHCF) is synthesized as a cathode material for aqueous NH4 + batteries and Fe2 (SO4 )3 is utilized as a kind of functional additive in the electrolyte based on the "common ion effect" to enhance its electrochemical performance. The results indicate that the initial capacity of FeHCF is about 80 mA h g −1 with a coulombic efficiency of 97.8%. The retention rate can attain 96.3% within nearly 1000 cycles. Multivariate analysis methods are carried out to characterize the mechanism of FeHCF in aqueous NH4 + batteries. From the practical standpoint, FeHCF has outstanding cycling stability and rate capability, making it feasible to be applied in the power grid.